A marble Sarcophagus of Gadara (Umm Qais), Jordan: insights on its provenance. (4th May 2022) - Al-Bashaireh, Khaled
Abstract : This research investigates the archaeometric characteristics of the marble sarcophagus displayed in the Umm Qeis Museum of Antiquities, Gadara (Umm Qais), north Jordan. Marble sarcophagi are very rarely found at archaeological sites in Jordan; the Gadara marble sarcophagus is, therefore, unique. This sarcophagus, dated to the 3rd century AD, presents only the base and the lid; the lid shows remnants and traces of the chiton and himation of two effigies, while the pedestal shows remnants of a foot and a weapon, both probably indicate an Attic sarcophagus. The research undertaken aims to determine the quarry origins of the box and the lid, while also considering the notion of some scholars that the boxes of Attic sarcophagi were carved of Pentelic marble, while the lids were carved of Hymettian marble. The results of the mineralogical, petrographic, chemical and isotopic analyses showed that the most likely quarry origin of the two marble parts is Pentelikon Mountain, Athens, Greece. The sarcophagus's high quality, elaborate decorations, large volume and heavy weight, along with the inland location of Gadara, suggest that it was ordered by a wealthy and/or a high-status Gadarene citizen.